2020
DOI: 10.1021/acs.chemrev.0c00576
|View full text |Cite
|
Sign up to set email alerts
|

Single-Atom Catalysts across the Periodic Table

Abstract: Isolated atoms featuring unique reactivity are at the heart of enzymatic and homogeneous catalysts. In contrast, although the concept has long existed, single-atom heterogeneous catalysts (SACs) have only recently gained prominence. Host materials have similar functions to ligands in homogeneous catalysts, determining the stability, local environment, and electronic properties of isolated atoms and thus providing a platform for tailoring heterogeneous catalysts for targeted applications. Within just a decade, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
631
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 860 publications
(688 citation statements)
references
References 987 publications
(3,502 reference statements)
5
631
0
2
Order By: Relevance
“…67 This type of study would cultivate a better understanding of OER catalysis from a comprehensive perspective, and furthermore would eventually bridge the gap between heterogeneous and homogeneous catalysis. [83][84][85] As described above, recent in situ and operando characterization studies captured the oxidation state of the active site and surface intermediate during the OER. The experimental evidence in Fig.…”
Section: Spectroscopic Evidence To Support the Claimed Catalytic Cyclmentioning
confidence: 99%
“…67 This type of study would cultivate a better understanding of OER catalysis from a comprehensive perspective, and furthermore would eventually bridge the gap between heterogeneous and homogeneous catalysis. [83][84][85] As described above, recent in situ and operando characterization studies captured the oxidation state of the active site and surface intermediate during the OER. The experimental evidence in Fig.…”
Section: Spectroscopic Evidence To Support the Claimed Catalytic Cyclmentioning
confidence: 99%
“…This process has gained enormous advancement by the advent of nanoscience and nanotechnology, more recently has found a revolutionary approach in the development of single‐atom catalysts (SACs). [ 15 ] In 2003, Saltsburg and Flytzani‐Stephanopoulos investigated Au and Pt in an ionic forms which were strongly associated with the surface of ceria and responsible for the water‐gas shift reaction. They reported that Pt or Au nanoparticles on the surface of ceria did not participate in the catalysis, the ionic form of Au or Pt on the surface of ceria has functioned as SACs.…”
Section: Introductionmentioning
confidence: 99%
“…Single-atom catalysts (SACs) have recently emerged as a new class of materials bridging the gap between the homogeneous and heterogeneous catalysis worlds. [1][2][3] These materials represent the utmost utilization of precious metals, while offering more facile preparation, handling, and recovery compared to traditional catalytic systems. 4,5 Due to the unsaturated coordination of the active center as well as quantum and support effects, over the past few years SACs were improved to show extraordinary catalytic activity and selectivity toward specific products in important transformations such as hydrogenation, oxidation, carbon-carbon coupling, water-gas-shift, and electrosynthesis.…”
Section: Introductionmentioning
confidence: 99%